Impact of sarcopenia on survival and late toxicity in head and neck cancer patients treated with radiotherapy. (June 2020) - van Rijn-Dekker, Maria I.; van den Bosch, Lisa; van den Hoek, Johanna G.M.; Bijl, Hendrik P.; van Aken, Evert S.M.; van der Hoorn, Anouk; Oosting, Sjoukje F.; Halmos, Gyorgy B.; Witjes, Max J.H.; van der Laan, Hans P.; Langendijk, Johannes A.; Steenbakkers, Roel J.H.M.
Highlights: Sarcopenia is relevant for head and neck cancer patients treated with radiotherapy. Sarcopenia is an independent adverse prognostic factor for survival outcomes. For oropharyngeal cancer, survival is more defined by p16 status than by sarcopenia. Sarcopenia is associated with late radiation-induced toxicities. Abstract: Background and purpose: Sarcopenia is emerging as an adverse prognostic factor for survival and complication risk in cancer patients. This study aims to determine the impact of sarcopenia on survival and late toxicity in a large cohort of head and neck squamous cell carcinoma (HNSCC) patients treated with definitive (chemo)radiotherapy ((C)RT). Materials and methods: HNSCC patients treated with definitive (C)RT from January 2007 to June 2016 were included. Sarcopenia was assessed from radiation planning computed tomography (CT) scans using skeletal muscles at level C3. The impact of sarcopenia on overall survival (OS) and disease-free survival (DFS) was evaluated using the Kaplan–Meier method. Multivariable association models were developed to assess the impact of sarcopenia on late toxicity. Results: The study population was composed of 750 HNSCC patients. Cut-off values for sarcopenia were set at SMI < 42.4 cm 2 /m 2 (men) and <30.6 cm 2 /m 2 (women) corresponding lowest gender specific quartile. Sarcopenic patients had significantly poorer survival rates, especially those with lower performance status and locally advanced disease. In oropharyngeal cancer patients, survival was more determined by p16 status than by sarcopenia. In multivariable analysis, sarcopenia was associated with worse OS (HR 0.72, p  = 0.012) and DFS (HR 0.67, p  = 0.001). In multivariable association models, sarcopenia was associated with physician-rated xerostomia six months after treatment (OR 1.65, p  = 0.027) and physician-rated dysphagia six and twelve months after treatment (OR 2.02, p  = 0.012 and 2.51, p  = 0.003, respectively). Conclusion: Sarcopenia in HNSCC patients receiving definitive (C)RT is an independent prognostic factor for worse survival outcomes and is associated with physician-rated toxicity.